Treatment of Spasticity in Cerebral Palsy - Gül Mete Civelek; Ayçe Atalay (Güncel Pediatri)
The cerebral palsy diagnosis is a clinical one and it includes motor development delay, abnormal muscle tone and hyperreflexia. Muscle weakness, spasticity, loss of coordination, the continuation of the primitive reflexes and non-developed normal motor control are often seen in children with cerebral palsy. Spasticity is the velocity dependent increase in the resistance against passive muscle stretching. Spasticity treatment program should be established after detailed evaluation of degree and effects.Treatments to achieve optimal muscle tone include physical therapy and rehabilitation program, oral and injectable medications and surgical treatments. In the treatment of spasticity, a personalized physical therapy and rehabilitation program including stretching exercises should be in the treatment plans, absolutely. There is no consensus regarding the optimal application of pharmacotherapy for the treatment of spasticity in cerebral palsy. Oral medications such as baclofen, benzodiazepine, tizanidine and dantrolene can be used for the treatment of generalized spasticity. Oral drugs have significant side effects such as sedation and cognitive deficits. Chemodenervation with perineural phenol or ethanol injection or intramuscular injection of botulinum neurotoxin A can be used as treatment of localized spasticity. It is shown that botulinum neurotoxin type A is safe and effective in reducing spasticity in children. Most commonly used surgical technique for the treatment of spasticity in cerebral palsy is selective dorsal rhizotomy and it can be applied to selected cases. Treatment options that are used in the treatment of spasticity in cerebral palsy are discussed in this review.